Γδ T cells in artiodactyls: Focus on swine. (March 2022) - Le Page, Lauren; Baldwin, Cynthia L.; Telfer, Janice C.
Abstract: Vaccination is the most effective medical strategy for disease prevention but there is a need to improve livestock vaccine efficacy. Understanding the structure of the immune system of swine, which are considered a γδ T cell "high" species, and thus, particularly how to engage their γδ T cells for immune responses, may allow for development of vaccine optimization strategies. The propensity of γδ T cells to home to specific tissues, secrete pro-inflammatory and regulatory cytokines, exhibit memory or recall responses and even function as antigen-presenting cells for αβ T cells supports the concept that they have enormous potential for priming by next generation vaccine constructs to contribute to protective immunity. γδ T cells exhibit several innate-like antigen recognition properties including the ability to recognize antigen in the absence of presentation via major histocompatibility complex (MHC) molecules enabling γδ T cells to recognize an array of peptides but also non-peptide antigens in a T cell receptor-dependent manner. γδ T cell subpopulations in ruminants and swine can be distinguished based on differential expression of the hybrid co-receptor and pattern recognition receptors (PRR) known as workshop cluster 1 (WC1). Expression of various PRR and other innate-like immune receptors diversifies the antigen recognition potential of γδ T cells. Finally, γδ T cells in livestock are potent producers of critical master regulator cytokines such as interferon (IFN)-γ and interleukin (IL)-17, whose production orchestrates downstream cytokine and chemokine production by other cells, thereby shaping the immune response as a whole. Our knowledge of the biology, receptor expression and response to infectious diseases by swine γδ T cells is reviewed here. Highlights: Swine are a γδ T cell high species Swine γδ T cells are heterologous Swine subpopulations are defined by WC1, CD2 and CD8 expression Swine γδ TCR diversity narrows with animal aging Swine γδ T cells are active participants in infectious disease Swine γδ T cells present antigen, produce IL-17 and IFN-gamma